Respuesta :
Answer: 2a -5 + h
Step-by-step explanation:
f(x) = x² - 5x
f(a + h) = (a + h)² - 5(a + h)
= a² + 2ah + h² - 5a - 5h
f(a) = a² - 5a
f(a + h) - f(a) = a² + 2ah + h² - 5a - 5h - (a² - 5a)
= a² + 2ah + h² - 5a - 5h - a² + 5a
= 2ah - 5h + h²
[tex]\frac{f(a + h) - f(a)}{h} = \frac{2ah - 5h + h^{2}}{h}[/tex] = 2a - 5 + h
this looks suspiciously like the difference quotient
anyway
evaluate each then put them together
[tex]f(a+h)=(a+h)^2-5(a+h)[/tex]
[tex]f(a+h)=a^2+2ah+h^2-5a-5h[/tex]
[tex]f(a+h)=a^2+2ah-5a-5h+h^2[/tex]
[tex]f(a)=a^2-5a[/tex]
so [tex]\frac{f(a+h)-f(a)}{h}=[/tex]
[tex]\frac{a^2+2ah-5a-5h+h^2-(a^2-5a)}{h}=[/tex]
[tex]\frac{a^2+2ah-5a-5h+h^2-a^2+5a}{h}=[/tex]
[tex]\frac{2ah-5h+h^2}{h}=[/tex]
[tex]2a-5+h[/tex]